2007
DOI: 10.1590/s0100-204x2007001000017
|View full text |Cite
|
Sign up to set email alerts
|

Características estruturais e produção de forragem em pastos de capim-mombaça submetidos a períodos de descanso

Abstract: Resumo -Este trabalho teve como objetivo avaliar as características estruturais, morfológicas e produtivas em pastos de capim-mombaça sob lotação rotacionada com três períodos de descanso, definidos conforme o número de novas folhas expandidas por perfilho: 2,5, 3,5 e 4,5 folhas. O delineamento experimental foi inteiramente casualizado com seis repetições, num total de 18 piquetes. Foram avaliadas as características: biomassa total, taxa de crescimento cultural, altura do dossel, relação folha/colmo, índice de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
30
0
23

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 16 publications
5
30
0
23
Order By: Relevance
“…Increasing light interception from 90 to 95% also increased the accumulation rates. This result is in agreement with several studies, which show higher average growth rate of the pasture when the incident light interception is around 95% (Mello & Pedreira, 2004;Cândido et al, 2005;Carnevalli et al, 2006;Barbosa et al, 2007;Gomide et al, 2007).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Increasing light interception from 90 to 95% also increased the accumulation rates. This result is in agreement with several studies, which show higher average growth rate of the pasture when the incident light interception is around 95% (Mello & Pedreira, 2004;Cândido et al, 2005;Carnevalli et al, 2006;Barbosa et al, 2007;Gomide et al, 2007).…”
Section: Resultssupporting
confidence: 93%
“…The smaller production of green forage mass by the cultivar BRS Kurumi was offset by its lower rest period (Table 3), which confers a higher number of grazing cycles (Table 4) and resulted in higher forage production of this cultivar during the rainy season. Gomide et al (2007), working with different rest periods, based on the number of green leaves per tiller in Mombaça grass, also observed that the greater number of cycles with shorter rest periods (appearance of 2.5 leaves per tiller) offsets the lower production of pre-grazing forage mass. Furthermore, the authors reported higher forage accumulation rates and a better leaf/stem ratio for this shorter rest period.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…The positive association between sward height and LI is well described for temperate grasses, and it has also been verified for tropical grasses, such as mombaça-grass (CARNEVALLI et al, 2006) and Tanzania-grass (BARBOSA et al, 2007). These latter observed that the conditions of 90, 95 and 100% of LI were achieved with canopy heights around 60, 70 and 85 cm, respectively, whereas Gomide et al (2007), when evaluating heights up to 117.2 cm of mombaça-grass pasture, have obtained maximum LI of 96.4%, similar to observed in this study at 90 cm of canopy height, i.e., under experimental conditions, it was achieved higher LI at heights lower than reported by other authors.…”
Section: Resultsmentioning
confidence: 57%
“…Furthermore, the canopy structure, especially in tropical forage, exerts direct effect on the process of ingestion and consumption of forage, by affecting the forage intake by the animal. In this way, the canopy characteristics, such as height, leaf density, leaf stem -1 ratio and proportion of dead material interfere with the consumption because alter the bite size, bite rate, and grazing time (GONÇALVES et al, 2009;PALHANO et al, 2007;REGO et al, 2006).…”
Section: Introductionmentioning
confidence: 99%